Copper Sulfide Nanoparticle‐Redirected Macrophages for Adoptive Transfer Therapy of Melanoma. (12th January 2021) - Xu, Jiaojiao; Zheng, Binbin; Zhang, Sihang; Liao, Xueling; Tong, Qinli; Wei, Guoguang; Yu, Sheng; Chen, Gaoxian; Wu, Aihua; Gao, Shuai; Qian, Yuyi; Xiao, Zeyu; et al.
Abstract: Adoptive cell therapy (ACT) has achieved landmark advances in treating cancer in clinic. Recent advances in ACT of macrophages engineered to express chimeric antigen receptors (CARs) have shown effectiveness in treating solid tumors. However, the CAR‐macrophage therapy is dependent on tumor antigen recognition and gene editing methods. Herein, an adoptive macrophage therapy is presented through copper sulfide nanoparticle‐regulation that exhibits substantial antitumor effect in melanoma‐bearing mice, without the need for tumor antigen repertoire. Bone marrow derived macrophages (BMDMs) incubated with the nanoparticles promote the cellular production of reactive oxygen species (ROS) through dynamin‐related protein 1 (Drp1)‐mediated mitochodrial fission. The high intracellular ROS level directs BMDMs polarization toward M1 phenotype by classical IKK‐dependent NF‐κB activation. Moreover, the copper sulfide nanoparticle‐stimulated BMDMs (CuS‐MΦ) reduce the expression of programmed death‐1 (PD‐1) and exhibit enhanced phagocytic and digestive ability. Intratumoral transfer of CuS‐MΦ significantly prolongs the median survival time of the tumor‐bearing mice, remodels the tumor microenvironment, and elicits systemic antitumor immunity. These results suggest a cancer therapeutic approach of adoptively transferred macrophages through the induction of intracellular ROS with nanomaterials. Abstract : Macrophages redirected with copper sulfide nanoparticles are applied to adoptive cell therapy against solid tumor. The copper‐induced intracellular reactive oxygen species polarizes the macrophages toward M1 phenotype, promotes phagocytosis and digestion of tumor cells, and triggers the local and systemic tumor‐suppressive alterations.